PENINGKATAN PERANAN WANITA MENUJU KELUARGA SEHAT DAN SEJAHTERA (P2WKSS) RW 6 KELURAHAN CIMUNCANG KECAMATAN GARUT KOTA - Esa Risi Suazini; Lina Humaeroh; Iin Patimah; Tri Wahyuni; Desy Syawianti; Ernawati; Tanti Suryawantie; Rosita Alvia; Fitri Hanriyani; Intan Rina Susilawati; Naning Suryani; Titi Purwitasari Handayani (Jurnal Pengabdian Masyarakat DEDIKASI, 2021)
Cimuncang sub district of Garut Kota is an urban area but has a low level of welfare, which is ranked the 6th poorest subdistrict in Garut Regency. The involvement of STIKes Karsa Husada Garut as one of the stakeholders in the Increasing the Role of Women towards a Healthy and Prosperous Family program (P2WKSS) is intended to be able to actively participate in theprogram. This activity for STIKes Karsa Husada is a community service activity which is oneof the obligations of Higher Education Institutions in implementing the Tri Dharma. Theplannedactivities to be carried out are increasing knowledgethrough growth and development trainingfor PAUD teachers, parents and cadres as well as ear shop activities, namely anti stunting stalls by providing food processing practices for children and family planning with longterm education methods. Implementation of activities in the PAUD RW 6 classroom, Cimuncang Village, Garut City District on Wednesday 17 November 2021 and Thursday 18 November 2021. Participants were attended by 12 participants on the first day and 11participants on the second day.